1999
DOI: 10.1128/jvi.73.3.1868-1877.1999
|View full text |Cite
|
Sign up to set email alerts
|

Factors Governing the Activity In Vivo of Ribozymes Transcribed by RNA Polymerase III

Abstract: In order to determine the parameters that govern the activity of a ribozyme in vivo, we made a systematic analysis of chimeric tRNAVal ribozymes by measuring their cleavage activities in vitro as well as the steady-state levels of transcripts, the half-lives of transcribed tRNAVal ribozymes, and their activities in both HeLa and H9 cells. These analyses were conducted by the use of transient expression systems in HeLa cells and stable transformants that express ribozymes. Localization of transcripts appeared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 55 publications
(94 reference statements)
0
63
1
1
Order By: Relevance
“…It forms two domains: the scaffold (domain 2) on which the ribozyme is built, and the active centre (the catalytic domain; known as domain 1; Cech & Uhlenbeck, 1994; Hammann & Lilley, 2002). During the past two decades, the mechanism of action of hammerhead ribozymes, describing the requirement for divalent metal ions, definition of the catalytic domains, and the sequence specificity, which is usually referred to as the target site, has been shown (Kawasaki et al ., 1996; Koseki et al ., 1999; Takagi et al ., 2001; Kato et al ., 2001; Akashi et al ., 2002; Hammann & Lilley, 2002; Pyle, 2002). The activity of ribozymes in vivo is dependent on the level of expression at which they are effective, their specificity, and their intracellular stability, target colocalization and the accessibility of target sites (Yarus, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It forms two domains: the scaffold (domain 2) on which the ribozyme is built, and the active centre (the catalytic domain; known as domain 1; Cech & Uhlenbeck, 1994; Hammann & Lilley, 2002). During the past two decades, the mechanism of action of hammerhead ribozymes, describing the requirement for divalent metal ions, definition of the catalytic domains, and the sequence specificity, which is usually referred to as the target site, has been shown (Kawasaki et al ., 1996; Koseki et al ., 1999; Takagi et al ., 2001; Kato et al ., 2001; Akashi et al ., 2002; Hammann & Lilley, 2002; Pyle, 2002). The activity of ribozymes in vivo is dependent on the level of expression at which they are effective, their specificity, and their intracellular stability, target colocalization and the accessibility of target sites (Yarus, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The former modification, the usage of the tRNA Val promoter, was to increase the efficiency of transport of Rz from nucleus to cytoplasm where Rz actually function to cleave the target mRNA 24. The latter modification was to enhance Rz activity by resolving RNA structure.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a crucial drawback for ordinary ribozymes such as hammerhead‐type or hairpin‐type in that they may remain in the nucleus and fail to be transported to the cytoplasm where they exert their function 23. To circumvent this problem, Koseki et al recently constructed an expression vector of ribozyme driven by the tRNA Val promoter, which allowed export of transcribed ribozymes from the nucleus to the cytoplasm and confirmed that the expression of ribozyme was indeed observed in the cytoplasm 24, although the ribozyme activity, measured as mRNA cleavage activity, was unexpectedly low 23–26. The most plausible reason for this low activity was that the secondary or tertiary structures of the target mRNA block ribozyme binding to the target sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Z tego względu regulowane w komórkach docelowych promotory typu Pol II mają znaczącą przewagę w terapii genowej. Ekspresja rybozymów z promotorów Pol II przebiega w cytoplazmie, w której jest obecny docelowy mRNA [99]. Na przykład promotor rodopsyny (typu Pol II) został wykorzystany w celu osiągnięcia wysokiego poziomu transkrypcji rybozymów, których ekspresja jest ograniczona do komórek pręcikowych fotoreceptorów siatkówki [26].…”
Section: Promotoryunclassified